Characteristics and Strategic Priorities of Pharmaceutical Companies’ Medical Departments in Portugal - Cruz-Duarte, Raquel (2025)
Introduction: Medical affairs have evolved over the last years from being a support function to a proactive and strategic pillar of pharmaceutical companies. Consequently, the characteristics and strategic priorities of medical departments have adapted to this constantly changing environment. The last study that characterized pharmaceutical companies´ medical departments was performed ten years ago, and many events have impacted their structure and priorities since then. Therefore, we aimed to perform an up-to-date characterization of the medical departments of the pharmaceutical companies operating in Portugal.Methods: An online anonymous survey developed by the Portuguese Association of Pharmaceutical Medicine (AMPIF) was sent to the medical department directors or general managers of 46 pharmaceutical companies. The data collected was analyzed using descriptive statistics.Results: Nineteen companies (41%) answered the survey. Medical departments have on average 20 workers and medical affairs is the most prevalent function, accounting for more than 75% of the headcounts, with medical science liaison (MSL) being the most frequent professional category. Medical departments’ staff has diverse academic backgrounds with more than half having, at least, a master’s degree. Medical education is the current strategic top priority area, while digital projects are indicated as the most emergent for the upcoming years. In 2022, companies answered an average of 921 medical information requests, led 72 clinical sessions and meetings, and performed a total of 28 740 interactions. On average six local studies were developed by the companies that answered this survey.Conclusion: This study allowed the characterization of the workforce, activities, and priorities of pharmaceutical companies’ medical departments operating in Portugal. The results are expected to serve as a basis for discussion about the Medical Departments’ strategic focus, enabling better adaptation to innovation and challenges faced by the sector.